Incidence and outcomes of neonatal group B streptococcal sepsis in Qatar-a multicentre study - Sajid Salim Thyvilayil; Anvar Paraparambil Vellamgot; Khalil Salameh; Sudheer Babu Kurunthattilthazhe; Abdurahiman Elikkottil; Liliana Llerena Dominguez; Dhanya Banarjee (BMC Pediatrics)
Abstract Background Group B Streptococcus (GBS) is the most common cause of neonatal early onset sepsis in term infants and a major cause of late onset sepsis in both term and preterm infants. Aim To estimate the incidence of GBSS among neonates born in Qatar between July 2015 and June 2020 (5 years). A secondary aim was to describe the outcomes of the affected babies. Materials and Methods A retrospective chart review of all neonates born during the study period was performed with the help of medical records departments of the four main maternity hospitals in Qatar, where > 90% of the births occurred. Results From 123,878 live births, 113 babies grew GBS in blood culture, during the first 90 days. 72 cases of early-onset GBS sepsis (EOGBSS) and 41 cases of late-onset GBS sepsis (LOGBSS) were identified. The estimated incidence of EOGBSS and LOGBSS were 0.58/1000 live births (95% CI 0.46- 0.73) and 0.33/1000 live births (95% CI 0.24- 0.45) respectively. The overall mortality was 7%, and the chart review identified severe neurodisability among at least 11% of survivors. Conclusion The incidences of EOGBSS and LOGBSS in Qatar are 0.58/1000 live births (LB) and 0.33/1000 LB, respectively. The relatively high incidence of EOGBSS probably reflects the high rate of carrier state among pregnant mothers. We did not observe any significant change in incidence after introducing the universal maternal screening for GBS. The overall mortality was similar to previously published data. Further prospective studies are recommended.